Pengaruh Penggunaan Aplikasi Zoom Cloud Meeting Terhadap Kinerja Guru Menggunakan Algoritma Decision Tree (C4.5) - Hadwitya Handayani Kusumawardhani; Aslam Fatkhudin (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2022)
It is also necessary to measure teacher performance in teaching and activities during school hours, because with the pandemic all aspects are hampered, including the education sector. The zoom cloud meeting application was chosen as one of the interactive learning media that is expected to maintain the continuity of education. In addition to the learning process, zoom cloud meetings are also used by teachers for other activities such as meetings, workshops and seminars. Therefore, it is necessary to calculate the performance of SMK Muhammadiyah Kesesi teachers who have used zoom cloud meetings. In calculating the effect of using the zoom cloud meeting application on the performance of SMK Muhammadiyah Kesesi teachers, data collection from the teachers was carried out in the form of a questionnaire, after the data was collected it would be processed with a decision tree classification using the C4.5 algorithm. This type of research is a classification with the concept of data mining which is categorized by: Influence and No Influence. In collecting data using a questionnaire and the variables used in this study were four, namely interest in learning, learning methods, teacher activities, and learning media. The method used in this research is the classification method.